Open space and heritage integration strategy in the 2035 Metropolitan Lima-Callao Urban Development Plan - Del Castillo Cáceres, Juan Manuel (2018)
One major contribution of the Metropolitan Lima Urban Development Plan 2035 (PLAM2035) to the history of planning is its innovative strategy to integrate the city’s open spaces and archaeological heritage within a network of green corridors for the enjoyment of the community. Most of Lima’s architectural heritage is located in the periphery of the metropolis, linked to river valleys and mountains, sites that have been converted into landfills or wastelands threatened by informal urbanisation. However, these places foster the potential to become ecological and cultural assets that help in connecting the metropolitan ecosystems with Andean heritage, to promote the protection of archaeological sites, tourism, national and international research activities, and community integration. This study seeks to analyse the PLAM2035’s proposal regarding the integration between the System of Open Spaces and Ecological Infrastructure and the Heritage and Landscape Network focusing on its context, its new conceptual vision, and its process.